Students' evaluation on lecturers using fuzzy numbers / Nazirah Ramli and Daud Mohamad - Ramli, Nazirah; Mohamad, Daud (2008)
This paper presents an alternative method for students' evaluation on lecturers based on fuzzy approach. Owing to vague concepts frequently represented in decision data and decision making processes, the crisp data are inadequate to model real life situations. In this study, fuzzy number arithmetic operations and fuzzy ranking methods are applied to deal with the problem of uncertainty in the evaluation process. An empirical study has been conducted in Universiti Teknologi MARA (UiTM) Pahang where the process of traditional evaluation is basically based on the calculation of mean. Eleven items in the traditional process of evaluation are categorised into three basic criteria that are teaching, class management and professional and motivational attitude. The fuzzy weight of each criterion is generated from the students' opinion. This method can evaluate the performance of lecturers in class in a more holistic and effective approach and may give great satisfaction to all parties involved in the decision making process.